2017
DOI: 10.1016/j.jvs.2016.07.128
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic comparison of stent configurations used for aortoiliac occlusive disease

Abstract: The studied aortoiliac stent configurations have distinct locations where flow disturbances occur, and these are related to the radial mismatch. The CERAB configuration is the most unimpaired physiologic reconstruction, whereas BMK and CK stents have their typical zones of flow recirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 35 publications
2
37
0
1
Order By: Relevance
“…The setup was based on a two-parameter Windkessel model, including a compliance chamber downstream of the phantom to simulate peripheral vessel impedance. 13 In brief, a pulsatile flow at a rate of 60 beats/min was generated with a physiologic flow rate in a range of 1.6 L/min (peak flow, 3.6 L/min). The inlet section consisted of a 1.2-m tube to ensure a fully developed laminar flow entering the model.…”
Section: Methodsmentioning
confidence: 99%
“…The setup was based on a two-parameter Windkessel model, including a compliance chamber downstream of the phantom to simulate peripheral vessel impedance. 13 In brief, a pulsatile flow at a rate of 60 beats/min was generated with a physiologic flow rate in a range of 1.6 L/min (peak flow, 3.6 L/min). The inlet section consisted of a 1.2-m tube to ensure a fully developed laminar flow entering the model.…”
Section: Methodsmentioning
confidence: 99%
“…In AA aneurysms, changes in flow patterns modulate inflammatory mechanisms in the vascular endothelium, causing aneurysm growth [4]. For AA aneurysms and stenotic lesions around the aortic bifurcation, in vitro data have shown that different treatment options generate different flow perturbations [5], [6], which can partly explain the different outcomes of these treatments. Post-treatment analysis of AA blood-flow patterns may make the follow-up schemes after endovascular treatment more patient-specific by predicting potential failure.…”
Section: Introductionmentioning
confidence: 99%
“…where C 1 = 1.281, C 2 = 0.064, C 3 = −1.03, C 4 = 0.885, C 5 = −0.166, and t is the time in second. The period T and coefficient C 1 were modified from 0.83 and 2.891 to produce zero end systolic velocity (ESV) and 60 beats per minute or 1 Hz (T = 1 seconds), resting heart rate to match the suprarenal profile used by Groot Jebbink et al 1 Infrarenal flow profile based on Fraser et al 16 was digitized manually with 100 time points at 10 ms intervals. The effective flow rate was adjusted from 13.3 to 12.5 mL and heart rate was adjusted from 64.5 to 60 beats/minute.…”
Section: Flow Profilesmentioning
confidence: 99%
“…Furthermore, it has been successfully used by researchers to study and validate new treatment methods such as minimally invasive endovascular stent treatments. 1,2 In addition,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation